Formal ESL Synthesis for Control-Intensive Applications. (27th June 2012) - Dossis, Michael F.
Abstract : Due to the massive complexity of contemporary embedded applications and integrated systems, long effort has been invested in high-level synthesis (HLS) and electronic system level (ESL) methodologies to automatically produce correct implementations from high-level, abstract, and executable specifications written in program code. If the HLS transformations that are applied on the source code are formal, then the generated implementation is correct-by-construction. The focus in this work is on application-specific design, which can deliver optimal, and customized implementations, as opposed to platform or IP-based design, which is bound by the limits and constraints of the preexisting architecture. This work surveys and reviews past and current research in the area of ESL and HLS. Then, a prototype HLS compiler tool that has been developed by the author is presented, which utilizes compiler-generators and logic programming to turn the synthesis into a formal process. The scheduler PARCS and the formal compilation of the system are tested with a number of benchmarks and real-world applications. This demonstrates the usability and applicability of the presented method.